Five new Napaeus species (Gastropoda: Pulmonata: Enidae) from Gran Canaria and El Hierro (Canary Islands) - Yanes, Yurena; Santana, Jesús; Artiles, Miguel; Deniz, Francisco; Martín, Javier; Alonso, María R.; Ibáñez, Miguel (Zootaxa, 2011)
Five new species of Napaeus are described, four from Gran Canaria and one from El Hierro (Canary Islands): Napaeus josei n. sp., N. venegueraensis n. sp., N. arinagaensis n. sp., N. validoi n. sp. and N. grohi n. sp. The main differences from the most similar species and data on distribution are presented. At least three of the new species disguise their shells with soil, presumably to avoid predation.